Association between mass media exposure and endorsement of HIV-infected female teachers' teaching: insight from 2014 Ghana Demographic and Health Survey - Francis Appiah; Justice Ofosu Darko Fenteng; Andrews Ohene Darteh; Felix Dare; Joel Afram Saah; Matthew Takyi; Patience Ansomah Ayerakwah; Kingsley Boakye; Edward Kwabena Ameyaw (BMC Women's Health, 2022)
Abstract Introduction Ghana recorded 19,931 new annual HIV infections in 2018 translating to 14,181 AIDS-related deaths. Mass media is capable of ensuring the sustainability of initiatives aimed at curbing HIV/AIDS epidemic by reducing HIV/AIDS stigma and discrimination. The study aimed at exploring if mass media plays a role in whether HIV-infected female teachers should be allowed to teach in Ghana. Materials and methods The study used women’s file of the 2014 Ghana Demographic and Health Survey (GDHS). The current study was restricted to 6025 women who had complete information on the variables analysed. Binary Logistic regression was conducted between mass media and the dependent variable whilst controlling for the effect of the significant covariates. The results were presented in odds ratio (OR) and adjusted odds ratio (AOR) at 95% confidence interval (CI). All analyses were carried out using STATA version 14.0. Results Generally, 51% of the women mentioned that HIV-infected female teachers should be allowed to teach in Ghana. Women who accessed mass media had higher odds of endorsing that HIV-infected female teachersshould be allowed to teach compared to those without access to mass media [AOR = 1.37, CI 1.200–1.555], just as among those  with secondary or higher education compared to those with no formal education [AOR = 1.30, CI 1.102–1.529]. Rural inhabitants had decreased odds of proclaiming that HIV-infected female teachers should be allowed to continue teaching compared with urban residents [AOR = 0.83, CI 0.717–0.957]. Conclusions Endorsement of HIV-positive female teachers’ continued teaching was associated with access to mass media. This is suggestive that various mass media platforms could help to reach the public with HIV/AIDS-related information, particularly those that touch on stigma and discrimination, which will potentially increase women’s knowledge and shape their perceptions about persons living with HIV.